Socialization of Domestic Waste Water Management Systems in Tallo Village - Ibrahim, Roslinda; Ali, Sumarni Hamid; Zubair, Achmad; Hustim, Muralia; Lando, Asiyanti Tabran; Sari, Kartika; Putri Mangarengi, Nur An-nisa; Abdullah, Nurjannah Oktorina; Damayanti, Annisa Dwi; Hanami, Zarah Arwieny (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
The urban slum problems are always be a complex issues in environmental physics, economic, social, and also the facilities and infrastructure itself. In general, the slum areas are not suitable to live in because basic facilities and amenities are not available in the residential environment. The aim of this Community Service activity is to increased community knowledge and understand regarding domestic wastewater management system. The method used to the goal is by implementing socialization activities in one of the areas that belong to the slum category. Implementation of the Activities at the office of Kelurahan Tallo, attended by twenty-five participants. The enthusiasm of the participants in taking part in socialization activities is high, it is evident from the seriousness in receiving material and the desire to ask questions as well as sharing information about the management of wastewater in the Tallo Village. The level of public understanding of the socialization material has increased from 4% – 12% to 16% - 72%. With the increase in public knowledge and understanding is expected to increase also the motivation to participate in environmental conservation efforts, especially those related to the sustainability of the aquatic environment.